Troop Deployment and Effective Peace Operations in Africa: African Union Mission in Darfur (AMIS) (2004-2006) - Williams, Dodeye Uduak (Mediterranean Journal of Social Sciences, 2012)
The African Union (AU) was set up in 2002 with one of its core objectives being to ensure Peace and Security in the continent.In response to this, the AU has been involved at various levels in peacekeeping activities involving deployment of troops. Given that thesuccess or failure of any peace operation is tied to the various components of the peace process, this paper examines the AMISintervention in Darfur in terms of its limitations as a useful model for troop deployment in future African peace operations. It finds that thesecurity situation in Darfur was a huge challenge to AMIS and its deployment to Darfur was flawed on several counts including a weakmandate and unclear terms of reference for the mission.